Interfragmentary Stability Influences Healing of Intra-articular Fractures. A Radiographic Study of Canine Femoral Condyle Fractures Repaired with Lag Screws - Francis, D. J.; Johnson, K. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
The influence of fracture stability on the healing of intra-articular fractures of canine medial femoral condyles repaired with lag screws was evaluated radiographically and at necropsy. In 14 dogs, one condylar fracture was repaired with stable interfragmentary compression using two 4.0 mm cancellous lag screws. In the contralateral stifle, the condylar fracture was apposed with a single 4.0 mm cancellous lag screw so that the bone fragments were unstable and had interfragmentary motion. In a control group (n = 4), an arthrotomy was performed and a lag screw inserted without creating a fracture in one stifle. In the contralateral stifle, a condylar fracture was created and not repaired.Radiographically stable fracture gaps were slightly wider at one month than immediately post repair, but at two and three months were healed completely. Unstable fractures remained incompletely healed at one, two and three months. Osteophytes were detectable radiographically at three months. Unrepaired fractures remained completely unhealed and these joints had severe osteophyte formation at one month. At necropsy, all joints with intra-articular fractures had some osteophytes and erosion of the medial tibial plateau articular cartilage. It was concluded that interfragmentary compression was a critical factor in fracture healing and that lack of stability caused delayed union, osteophyte development and cartilage erosion.A model was developed to permit the study of the healing of both stable and unstable condyle repair.
Keywords: Intra-articular fracture; Lag screw fixation; Interfragmentary stability; Fracture healing; Radiology; Articular cartilage